Resisting the Obvious: State Policy Initiatives for Rural School Improvement Should Not Mean Just Another Round of Massive School Reorganization - E. Robert Stephens (Journal of Research in Rural Education, 1986)
Conditions are such in many states that we are likely to witness a renewed interest in school reorganization as the sole policy response to solving the rural school improvement issue. This essay advances three main lines of argument that suggest this approach ought to be resisted: the benefits of reorganization are mixed; the strengths of good rural schools are many and ought not to be ignored; and, the demise of the rural school will damage the infrastructure of the large expanses of this nation that are rural.